Thermal and flexural properties of regenerated cellulose (RC)/Poly(3- hydroxybutyrate)(PHB) biocomposites - Lee, Chiau Yeng (2015)
Regenerated cellulose (RC)/ poly(3-hydroxybutyrate) (PHB) composite were prepared by melt compounding with different RC content from 1 to 7 wt.%. Regenerated cellulose fiber was prepared in NaOH/urea aqueous solution. Properties of the cellulose and regenerated cellulose were compared using Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetric analysis (TGA) and Differential Scanning Calorimetry (DSC). Results of TGA and DSC revealed that the regenerated cellulose has lower thermal properties than cellulose. FTIR of regenerated cellulose showed that few peaks intensity were reduced or disappeared as compared to cellulose. PHB composites were characterized using TGA and flexural testing. Thermal stability of the composites insignificant changed with the incorporation of RC. Improvement in flexural strength and modulus were observed and 3 wt.% was found to be the optimum RC content.